Native and enzymatically modified wheat (Triticum aestivum L.) endogenous lipids in bread making: A focus on gas cell stabilization mechanisms. (1st April 2015) - Gerits, Lien R.; Pareyt, Bram; Masure, Hanne G.; Delcour, Jan A.
Highlights: Lipase impact on bread making depends on its dose and on the baking test scale. DATEM impact extensibility of freshly mixed dough whereas lipase use did not. Changes in dough extensibility were related to its lipid composition during mixing. Increasing polar lipid levels in dough liquor positively affects gas cell stability. Lipases alter the lipid composition and create a more uniform crumb structure. Abstract: Lipopan F and Lecitase Ultra lipases were used in straight dough bread making to study how wheat lipids affect bread loaf volume (LV) and crumb structure setting. Lipase effects on LV were dose and dough piece weight dependent. The bread quality improving mechanisms exerted by endogenous lipids were studied in terms of gluten network strengthening, which indirectly stabilizes gas cells, and in terms of direct interfacial gas cell stabilization. Unlike diacetyl tartaric esters of mono- and diacylglycerols (DATEM, used as control), lipase use did not impact dough extensibility. The effect on dough extensibility was therefore related to its lipid composition at the start of mixing. Both lipases and DATEM strongly increase the levels of polar lipids in dough liquor and their availability for and potential accumulation at gas cell interfaces. Lipases form lysolipids that emulsify other lipids. We speculate that DATEM competes with (endogenous) polar lipids for interacting with gluten proteins.